2021
DOI: 10.1016/j.mathsocsci.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Inflation, endogenous quality increment, and economic growth

Abstract: This study explores the effects of monetary policy in a Schumpeterian growth model with endogenous quality increment and distinct cash-in-advance (CIA) constraints on consumption, manufacturing and R&D investment. Our results are summarized as follows. When the CIA constraint is solely on consumption expenditure, an increase in the nominal interest rate may stifle economic growth by lowering the arrival rate of innovation and stimulate it at the same time by raising the size of quality increment. An additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 63 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…In fact, an increase of 1% of INF decreases economic growth by 1.8%. This result is similar to the results presented by Hu et al (2022), Mandeya and Ho (2022), and Sequeira (2021), who found that inflation negatively harms economic growth in both the short and long run. On the other hand, adverse economic effects dominate if inflation rises faster.…”
Section: Resultssupporting
confidence: 92%
“…In fact, an increase of 1% of INF decreases economic growth by 1.8%. This result is similar to the results presented by Hu et al (2022), Mandeya and Ho (2022), and Sequeira (2021), who found that inflation negatively harms economic growth in both the short and long run. On the other hand, adverse economic effects dominate if inflation rises faster.…”
Section: Resultssupporting
confidence: 92%
“…A high inflation rate reflects an economic malaise. Its adverse effects on economic growth (for example, through lower investment and efficiency) have been documented in the literature (e.g., Christiansen et al, 2013;Hu et al, 2021;Levine and Renelt, 1992;Levine and Zervos, 1993;Slemrod, 1995). We expect that a stable macroeconomic environment (proxied by a lower inflation rate) is associated with a higher per capita income.…”
Section: Effect Of Inflationmentioning
confidence: 86%
“…In this subsection, we alter the value of the innovation arrival rate to perform the robustness checks by considering two alternative values of I N ∈ {0.08, 0.15} accordingly to Hu et al (2021) and Caballero and Jaffe (1993), respectively. Keeping other parameters unchanged, we redo the numerical analysis by increasing the τ S and τ N respectively.…”
Section: Robustness Check On the Innovation-arrival Ratementioning
confidence: 99%